Task-specific policy capacities: A comparative analysis of cash transfer programs in Latin America and the Caribbean during the pandemic - Guillermo M. Cejudo; Cynthia L. Michel; Pablo de los Cobos (International Review of Public Policy)
The COVID-19 pandemic required simultaneous, effective policy responses from numerous policy sectors. How have policy capacities enabled these responses? This paper analyzes social policy responses in Latin America and the Caribbean. We compare how policy capacities enabled 27 LAC governments to respond to the social effects of the pandemic with 122 cash transfer programs. The paper is based on a quantitative analysis of the number, type, and coverage of the programs implemented in each country, and on qualitative information about the process by which governments identified beneficiaries and delivered the transfers. We argue that policy capacities are not only context-specific but also task-specific. They are not generic assets valuable for addressing all kinds of policy issues at all moments of the policy process. By analyzing how policy capacities were used, built, and deployed during the pandemic, we show how different combinations of policy capacities enabled governments to reach their populations and provide assistance in response to this emergency.Our analysis extends current discussions about how policy capacities can be operationalized in specific contexts, shows the importance of looking at different configurations of capacities to understand policy actions, and offers a comparative account of social policy responses in the region.